Answer:
( x − 4 ) ( x − 8 ) is the factorised form of the expression.
Explanation:
x
2
−
12
x
+
32
We can Split the Middle Term of this expression to factorise it.
In this technique, if we have to factorise an expression like
a
x
2
+
b
x
+
c
, we need to think of 2 numbers such that:
N
1
⋅
N
2
=
a
⋅
c
=
1
⋅
32
=
32
AND
N
1
+
N
2
=
b
=
−
12
After trying out a few numbers we get:
N
1
=
−
8
and
N
2
=
−
4
(
−
8
)
⋅
(
−
4
)
=
32
, and
(
−
8
)
+
(
−
4
)
=
−
12
x
2
−
12
x
+
32
=
x
2
−
8
x
−
4
x
+
32
=
x
(
x
−
8
)
−
4
(
x
−
8
)
(
x
−
8
)
is a common factor to each of the terms.
(
x
−
4
)
(
x
−
8
)
is the factorised form of the expression.